The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1038/clpt.2009.62
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Coadministration Potentiates the Effects of “Ecstasy” on Heart Rate and Temperature in Humans

Abstract: This study assessed the acute physiologic effects over time of (co)administration of Delta9-tetrahydrocannabinol (Delta9-THC) (the main psychoactive compound of cannabis) and 3,4-methylenedioxymethamphetamine (MDMA or "ecstasy") in 16 healthy volunteers. Pharmacokinetics and cardiovascular, temperature, and catecholamine responses were assessed over time. Both single-drug conditions robustly increased heart rate, and coadministration showed additive effects. MDMA increased epinephrine and norepinephrine concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 45 publications
0
32
3
Order By: Relevance
“…Second, both clonidine and MDMA bind to ␣ 2 -adrenergic receptors (Battaglia et al, 1988;Lavelle et al, 1999), and some ␣ 2 agonistic actions in the peripheral NE system have been documented for MDMA in vitro (Lavelle et al, 1999). However, in contrast to clonidine, MDMA increased plasma NE levels and blood pressure in the present and previous studies (Dumont et al, 2009;Hysek et al, 2011), indicating that the ␣ 2 agonistic effects of MDMA are not relevant for its main action in humans or are outweighed by the transporter-mediated release of NE and other monoamines.…”
Section: Discussioncontrasting
confidence: 53%
“…Second, both clonidine and MDMA bind to ␣ 2 -adrenergic receptors (Battaglia et al, 1988;Lavelle et al, 1999), and some ␣ 2 agonistic actions in the peripheral NE system have been documented for MDMA in vitro (Lavelle et al, 1999). However, in contrast to clonidine, MDMA increased plasma NE levels and blood pressure in the present and previous studies (Dumont et al, 2009;Hysek et al, 2011), indicating that the ␣ 2 agonistic effects of MDMA are not relevant for its main action in humans or are outweighed by the transporter-mediated release of NE and other monoamines.…”
Section: Discussioncontrasting
confidence: 53%
“…The cannabinoid system is an important regulator of noradrenergic systems in part via CB1 receptors (Reyes et al, 2009;Carvalho and Van Bockstaele, 2012;Cathel et al, 2014) and downregulation of CB1 receptors in CA (Hirvonen et al, 2012) could underlie the attenuated responses to MP-induced changes in metabolism observed in these brain regions. A prior study in CA showed that co-administration of Δ-9-tetrahydrocannabinol (THC) with ecstasy, which like MP is a monoamine transporter blocker, enhanced its cardiovascular effects and the increases in epinephrine and norepinephrine in plasma (Dumont et al, 2009). This is indicative of enhanced effects to ecstasy when CB1 receptors are co-stimulated by THC.…”
Section: Effects Of Mp On Brain Metabolism In Ca and Hcmentioning
confidence: 85%
“…Researchers in Australia did a compilation of hyperthermia case reports (n=69) from MDMA and found a clear correlation of the fatality rate and the body temperature at the arrival in the emergency room (20% for temperature < or equal to 39.5°C, 78% for temperature > 42.5°C) [148]. The temperature increase was shown to be longer if cannabis was used with MDMA and the heart rate was increased [149]. The same team searched for other acute adverse reactions to MDMA and found in total ten cases of seizures without hyperthermia, twelve cases of cerebrovascular accident, and six cases (all fatal) of cardiac events.…”
Section: Resultsmentioning
confidence: 99%